Social Work and algorithmic decision-making: The use of artificial intelligence in judicial promotion and protection proceedings (Research, Society and Development, 2026)
In Portugal, the decision-making of judicial magistrates in legal proceedings for promotion and protection is based, in particular, on the work of social workers from the Multidisciplinary Court Advisory Teams (EMAT), who are responsible, for example, for preparing reports and social information and are subject to evident pressure to reach the best decisions regarding the situation of the child or young person. Artificial intelligence (AI) is presented as a resource to ensure greater efficiency in the decision-making process of social workers. However, using this technology to prepare reports or social information accepted as evidence in judicial proceedings for promotion and protection raises legitimate concerns about the impact of AI on judicial decisions. In this article, we aim to demonstrate that, although it is possible to use an AI platform to prepare a social report in the context of a promotion and protection case, the use of this type of technology calls into question the decision-making of judicial magistrates and, consequently, the administration of justice. We conclude that the inability to reconstruct the path taken by the judge to reach a decision, as well as the difficulty in explaining their reasoning, which may be compromised by evidence produced by AI, threatens the impartiality and independence of judicial decisions, in accordance with national and international legal instruments. We believe that the use of AI by judicial actors must necessarily preserve all mechanisms that allow for the control and scrutiny of the decision-making process by the judicial magistrate.